SCIENTIFIC JUSTIFICATION FOR PLANNING THE ORGANIZATION OF DENTAL CARE FOR WORKERS IN CONTACT WITH EPOXY RESIN - Bobur B. Sattorov; Nodira Sh. Nazarova (Central Asian Journal of Medicine, 2024)
In the oral cavity of workers in the production of plastic products, chemical compounds as toxic dust can settle in the form of plaque in the area of the necks of the teeth, or through the damaged mucous membrane for faster penetration and absorption, which causes serious consequences in the form of periodontitis, stomatitis. The harm caused by chemicals to certain organs depends on the amount (dose) of these chemicals absorbed by the body. Inflammatory diseases, as well as periodontal damage, have an etiological connection with a violation of the microbiocenosis of the oral cavity. The constant influence of chemical compounds in low concentrations in the air and on the oral mucosa can contribute to a change in the composition of saliva, the structure of microbiocenosis, which eventually leads to a secondary deterioration in the hygienic condition of the oral cavity.